(3GdLQYI GdUGajI hGdfaMI GdcGajIs - (3GdeNJGQ Hf CMeO Hf CHj HcQ GdcfJj,J (B1227 (3g` s ((3GdCejf Ce Hf eMeO Hf YHO GdJGbGWi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd bdhH ChdjGFI eYOfG ddeUGaGI heQcRkG ddecGTaGJ hhab dJCdja gPG GdcJGH GdPi de jfSL fGSL Ydi eKdg aLGA eJfGSHkG ZGjI GdefGSHI , djS ajg bhd JeLg GdCSeGY , hdG eYfi dGjMUd efg GdEeJGY hdPdc SejJg LeYJg ef eJhf GdUMGM GdSs
(3BNQgG (B:s
(3Ke ENJda GdeGfYhf (B: (3gd Gdfgi eMehd Ydi GdJMQje , Ch cQGgI GdJfRjg , Ch NdGa GdChdi , Ydi KdGKI CbhGd McGgG Gdfhhi ai cJGH GdCPcGQ Cfg ecQhg dCfg ef TYGQ Cgd GdCghGA hGdHOY hcGf GdaQGZ ef JUfja s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3cJHJ HYV YHGQGJgG HGdMeQI s
(3cJHgG fGSNgG dCNjI ai Gddg Cced Hf eMehO GdYdhTi s
(3aQZ eDdag ef JUfjag ZQI Pi GdbYOI ef YGe (B1207(3g` s
Keywords: (3Gdabg GdESdGejs